Creating Physical Education in Remote Australian Schools: Overcoming the Tyranny of Distance through Communities of Practice - Tony Rossi; Karen Sirna (Journal of Research in Rural Education, 2008)
This paper reports on a qualitative case study undertaken in a remote part of Queensland, Australia. While there is some modest agreement about the capacity of contemporary information technologies to overcome the problems of schooling in areas of extreme remoteness, generally, children educated in such contexts are considered to be disadvantaged. The experiential areas of the curriculum, which often require specific teaching expertise, present the greatest challenge to teachers, and of these, physical education is perhaps the most problematic. This research reports on a case study of three remote Queensland multi-age primary (elementary) schools that come together to form a community of practice to overcome the problems of teaching physical education in such difficult circumstances. Physical education is constructed in these contexts by blurring the school and community boundaries, by contextualizing the subject content to make it relevant, and by adjusting the school day to accommodate potential physical education experiences. Each community gathers its collective experience to ensure the widest possible experiences are made available for the children. In doing so, the children develop a range of competencies that enable seamless transition to boarding high schools.